The feasibility of increasing the success of tuberculosis programs through drug ingestion supervisors in remote areas - La Jumu (Institute of Computer Science (IOCS), 2023)
called PMO) program is a signal of novelty to increase the acceleration of the success of the tuberculosis eradication program. However, the certainty of its feasibility in remote areas is not yet known. The purpose of this study is to find out the feasibility of the PMO program in remote areas. This quantitative method research was conducted in Biak Numfor, Papua, with total respondents of 23. The primary data was obtained from instruments of a set of questionnaires which were distributed randomly to family members of TB patients. The inclusion criteria were family members of TB patients who were currently on treatment and lived in Yendidori district, Biak. The exclusion criteria were family members of TB patients outside Yendidori, and not taking TB drugs. Secondary data was obtained from reputable journals. Data analysis was carried out descriptively. The results of the study showed that the PMO program had great support from TB client families, and were willing to be part of the program. Found cases of multidrug-resistance (26%), ignorance of drug consistency (100%) considering that 5 out of 18 clients were toddlers. The other major challenges were infrastructure conditions and geography, and lack of means of communication. In conclusion, the PMO program was considered to provide benefits and was feasible to implement to support the increase in the success of TB eradication programs involving family members.